The effect of mental fatigue on critical power during cycling exercise - Salam, H.; Marcora, S. M.; Hopker, J. G. (European Journal of Applied Physiology, 2018)
Purpose: Time to exhaustion (TTE) tests used in the determination of critical power (CP) and curvature constant (W') of the power-duration relationship are strongly influenced by the perception of effort (PE). This study aimed to investigate whether manipulation of the PE alters the CP and W'. Methods: Eleven trained cyclists completed a series of TTE tests to establish CP and W' under two conditions, following a mentally fatiguing (MF), or a control (CON) task. Both cognitive tasks lasted 30 min followed by a TTE test. Ratings of PE and heart rate (HR) were measured during each TTE. Blood lactate was taken pre and post each TTE test. Ratings of perceived mental and physical fatigue were taken pre- and post-cognitive task, and following each TTE test. Results: Perceived MF significantly increased as a result of the MF task compared to baseline and the CON task (P < 0.05), without a change in perceived physical fatigue (P > 0.05). PE was significantly higher during TTE in the MF condition (P < 0.05). Pre-post blood lactate accumulation was significantly lower after each TTE in MF condition (P < 0.05). HR was not significant different between conditions (P > 0.05). Neither cognitive task induced any change in CP (MF 253 ± 51 vs. CON 247 ± 58W; P > 0.05), although W' was significantly reduced in the MF condition (MF 22.8 ± 4.5 vs. CON 29.3 ± 6.3 kJ; P < 0.01). Conclusion: MF has no effect of CP, but reduces the W' in trained cyclists. Lower lactate accumulation during TTE tests following MF suggests that cyclists were not able to fully expend W' even though they exercised to volitional exhaustion.